PENGARUH KEDISIPLINAN MEMBACA AL-QUR’AN DAN AKHLAK TERHADAP PRESTASI BELAJAR SANTRI I’DAAD SD SHIGAR PUTRA PONDOK PESANTREN TAHFIZH DAARUL QUR’AN - Maryati Maryati (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
This research was conducted to determine the discipline of reading Al-Qur'an and morality towards the achievement of the sixth grade in learning Al-Qur'an at primary boarding school for boys of I'daad Shigar, Daarul Qur'an Islamic Boarding School. This research is a quantitative research with a survey method. Data collection techniques for disciplinary variable reading Al-Qur'an and morality were obtained through questionnaires that had been tested for validity and reliability. Data analysis techniques were carried out statistically with Crosstab techniques using the SPSS version 20 program involving 32 correspondents. From the research it can be produced that the influence of the discipline of Al-Qur'an reading and morality on Al-Qur'an learning achievement has a significant relationship between the two disciplinary and moral variables on students' learning achievement. Based on the results of calculations in statistics, it can be concluded: (1) Al-Qur'an learning achievement is influenced by Al-Qur'an reading discipline. (2) Al-Qur'an learning achievement is influenced by morals. (3) there is a positive relationship between the discipline of Al-Qur'an reading and morality towards the learning achievement of the Al-Qur'an students. This study can provide a positive contribution in building the discipline of students and the development of educational supervision techniques, especially in the supervision of the Al-Qur'an learning system, so it can encourage the improvement of quality in education.